CONDITION ENVIRONMENTAL THE CITY OF DIAMANTE DO OESTE – PR - Pinto, L. P.; Mari, A. C. C.; Mari Junior, A.; de Azevedo, K. D.; Cabral, C.; Frigo, E. P. (Revista Brasileira de Engenharia de Biossistemas, 2016)
The Environmental Health Indicator (ISA) was established in 1999 with purpose to analyze the efficiency of public policy, which seeks to improve the quality of life of the population. Can be applied in several cities, because it is an instrument that characterizes the basic sanitation. The objective of this study is to analyze the state of environmental health in the municipality of Diamante do Oeste - Paraná and evaluate the quality of services provided to the city through ISA. From quantitative data they are inserted into a formula used in this methodology, it is possible to define the health of a certain city. This study was realized in the municipality of Diamante do Oeste - PR, checking your health worth 81.67, which is considered healthy then being a place with quality of life.